Testing overwork weakness in Charcot‐Marie‐tooth disease: Is it true or false? - Prada, Valeria; Mori, Laura; Accogli, Susanna; Rivarola, Matteo; Schizzi, Sara; Hamedani, Mernhaz; Schenone, Angelo (Journal of the peripheral nervous system, 2018)
The occurrence of the overwork weakness (OW) in Charcot‐Marie‐tooth (CMT) disease has been debated for a long time. Especially at the hands level, it is still unclear as to whether OW occurs. Contrasting results may relate to the different muscle groups evaluated and the instruments used. We concentrated to the upper limbs (UL). We recruited 120 subjects, 60 CMT patients and 60 normal controls and evaluated the strength of the tripod pinch and of the hand‐grip with a dynamometer, the opposition ability with the thumb opposition test (TOT) and applied an innovative instrumental testing of hand function using the sensor engineered glove test (SEGT), which previously demonstrated its sensitiveness to measure severity of hands dysfunction in CMT patients. In CMT patients, TOT scores were significantly higher in the non‐dominant hand (NDH) compared to dominant hand (DH), strength in the NDH was slightly but not significantly better than the DH. Finally, SEGT results were similar between the NDH and DH, whereas in normal controls the DH performed better. In conclusion, this study supports the existence of the overwork weakness in CMT. We can speculate that the dexterity and overall ability of the hands appear more impaired in the DH as a result of a weakness and incapacity of opposition. Our results support the importance of avoiding supramaximal exercises and educating patients to prevent incorrect movements.